Generalized two point boundary value problems. existence and uniqueness. (1992) - Murty, K. N.; Sivasundaram, S.
Abstract : An algorithm is presented for finding the pseudo-inverse of a rectangular matrix. Using this algorithm as a tool, existence and uniqueness of solutions to two point boundary value problems associated with general first order matrix differential equations are established.